(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the thermophosphate associated with mulch and foliar levels of nutrients in aceroleira cultivated in Alta Paulista. The study was conducted in a commercial orchard of acerola cv. Olivier located in Irapuru/SP. The treatments were 1- Witness (T), 2- Witness plus mulch (CM), the straw being directed under the fruit canopy, 3- Witness with mulch and application of the Yoorin® temophosphate, and 4- Witness with application of Yoorin® directly in the soil. An experimental block design was used, with 4 treatments and 5 repetitions. The data were subjected to analysis of variance for the F Test and the means compared by the Tukey Test at the 5% level of significance. It was concluded that the use of thermophosphate and mulch are associated with high yields ensuring good levels of nutrients in the leaves of aceroleira cv. Olivier, with the exception of iron and potassium that were deficient. The excess of calcium, boron and manganese was not caused by the use of thermophosphate and mulch. Leaf diagnosis is a useful tool in the management of fertilization, being indicated before and during the harvest to improve the management of fertilization and thus avoid deficiency or excess of nutrients that can decrease the production potential of acerola.